2021
DOI: 10.1155/2021/6640624
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening Based on QSAR and Molecular Docking of Possible Inhibitors Targeting Chagas CYP51

Abstract: Chagas is a neglected tropical disease caused by the parasite Trypanosoma cruzi with no effective treatment in all its forms. There is a need to find more effective therapeutic alternatives with reduced toxicity. In this contribution, multiple linear regression models were used to identify the molecular descriptors that best describe the inhibitory activity of 52 fenarimol analogues against Trypanosoma cruzi. The topological, physicochemical, thermodynamic, electronic, and charge descriptors were evaluated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A particularly appealing yet somewhat less common approach to virtual screening is presented by QSAR equations derived from easy to calculate 1D, 2D and sometimes global 3D descriptors. Several such studies were reported in the literature, and in most cases, the descriptors were calculated for the ligands in their unbound states [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Some of these efforts were summarized in several review articles [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…A particularly appealing yet somewhat less common approach to virtual screening is presented by QSAR equations derived from easy to calculate 1D, 2D and sometimes global 3D descriptors. Several such studies were reported in the literature, and in most cases, the descriptors were calculated for the ligands in their unbound states [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Some of these efforts were summarized in several review articles [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…CYP51 inhibits the sterol synthesis, which is lethal to the parasite. Ravuconazole and posaconazole act through the coordination of nitrogen with heme iron into the binding cavity of CYP51 [ 59 ]. Studies on animal models found that posaconazole could be used for the treatment of acute and chronic CD [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The model function is trained using data from all molecules except one during the validation step. The properties of the model were then used to predict the pIC 50 for the chemical that wasn't included in the study [15][16][17][18][19]. The quality of the suggested QSAR models was assessed using statistical indicators such as Q 2 (Cross-validated correlation coe cient), R 2 (Regression coe cient), SD (Standard deviation) and SE (Standard error):…”
Section: Model Validationmentioning
confidence: 99%